All's well - Awad, Mona (Simon & Schuster, 2021)
"ALL'S WELL is about Miranda Fitch whose life is a waking nightmare after an accident ruins her acting career, and leaves her with chronic back pain, a failed marriage, and a deepening dependence on painkillers and alcohol. On the verge of losing her job as a college theater director, Miranda lives out her broken dreams through an upcoming production of Shakespeare's All's Well That Ends Well, when the unimaginable happens. She suddenly recovers, but at what cost?"--